1983
DOI: 10.1200/jco.1983.1.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor estrogen and progesterone receptor levels on the response to tamoxifen and chemotherapy in primary breast cancer.

Abstract: In 1977 the National Surgical Adjuvant Breast and Bowel Project initiated a prospectively randomized clinical trial for women with primary operable breast cancer and positive axillary nodes. In this study 1891 patients were randomized to receive L-phenylalanine mustard and 5-fluorouracil (PF) either with or without tamoxifen (T). In this interim report findings are presented concerning disease-free survival (DFS) and survival as related to age and to estrogen receptor (ER) and/or progesterone receptor (PR) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
1
2

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(99 citation statements)
references
References 9 publications
5
91
1
2
Order By: Relevance
“…In current clinical practice, the response to hormone therapy is associated with the levels of both estrogen receptors (ERs) and progesterone receptors (PRs) in both primary (Fisher et al, 1983;Rose et al, 1985;Harvey et al, 1999) and advanced (Valavaara et al, 1990;Harvey et al, 1999;Elledge et al, 2000) breast cancers. In the current receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, the response to hormone therapy is associated with the levels of both estrogen receptors (ERs) and progesterone receptors (PRs) in both primary (Fisher et al, 1983;Rose et al, 1985;Harvey et al, 1999) and advanced (Valavaara et al, 1990;Harvey et al, 1999;Elledge et al, 2000) breast cancers. In the current receptor.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Accurate determination of biomarkers is essential for the proper management of breast cancer patients. [3][4][5][6][7][8] The HER2 is overexpressed in B15-20% of breast carcinomas. [9][10][11] HER2 positivity is associated with higher rate of recurrence and mortality in newly diagnosed breast cancer patients, and agents that target HER2 are found to be effective in both the metastatic and adjuvant settings, reducing the risk of recurrence and mortality in patients with early stage disease.…”
mentioning
confidence: 99%
“…Among postmenopausal women, earlier studies have shown a significant trend in reduction of recurrence rate with higher ER levels among tamoxifen treated, supporting the significance of stronger ER content in endocrine treatment [5][6][7][8].…”
Section: Discussionmentioning
confidence: 91%
“…Remaining research questions include the benefit of LHRH agonists, in addition to tamoxifen, and if LHRH agonists have a role among those not achieving amenorrhea during cytotoxic chemotherapy. Moreover, efficacy of endocrine treament in relation to estrogen receptor (ER) status is mainly established among postmenopausal women, and the different endocrine milieu in premenopausal women may affect the predictive ability of ER status [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%